The optimization of muzāra’ah contracts in Islamic financial institutions for alleviating poverty and empowering the community's economy - Hamzah, Moh. (IAIN Syekh Nurjati Cirebon, 2024)
Poverty is a complex issue that affects various crucial sectors such as education, health, and agriculture. Islamic financial institutions play a significant role in addressing poverty through community empowerment in the agricultural sector. This research aims to examine the contribution of the muzāra’ah contract in economic empowerment and poverty alleviation. The research method used is a conceptual approach. The results show that the use of the muzāra’ah contract by Islamic financial institutions significantly contributes to reducing poverty in the agricultural sector. Additionally, Everett Rogers' Diffusion of Innovation theory can be used to enhance community understanding and acceptance of Islamic financial products. These findings make an important contribution to academic literature and offer effective strategies for economic empowerment through Islamic financial institutions.Keywords: Muzāra’ah; Economic Empowerment; Poverty; Sharia Financial Institutions.